2007
DOI: 10.1161/circresaha.107.154377
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Sensing Ion Channels Contribute to Transduction of Extracellular Acidosis in Rat Carotid Body Glomus Cells

Abstract: Abstract-Carotid body chemoreceptors sense hypoxemia, hypercapnia, and acidosis and play an important role in cardiorespiratory regulation. The molecular mechanism of pH sensing by chemoreceptors is not clear, although it has been proposed to be mediated by a drop in intracellular pH of carotid body glomus cells, which inhibits a K ϩ current. Recently, pH-sensitive ion channels have been described in glomus cells that respond directly to extracellular acidosis. In this study, we investigated the possible molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 52 publications
3
72
0
2
Order By: Relevance
“…To our knowledge, ASIC have not been reported in postganglionic sympathetic neurons in the SCG, and the low levels of ASIC we observed in this structure may be expressed by SIF cells in the ganglion. SIF cells are functionally and morphologically similar to carotid body type I cells, which do express ASIC (7,43,46). ASIC3 expression has been previously reported in normal NG, as well as PG (13).…”
Section: L988 Asic Expression In Chemoafferent Neuronssupporting
confidence: 57%
See 1 more Smart Citation
“…To our knowledge, ASIC have not been reported in postganglionic sympathetic neurons in the SCG, and the low levels of ASIC we observed in this structure may be expressed by SIF cells in the ganglion. SIF cells are functionally and morphologically similar to carotid body type I cells, which do express ASIC (7,43,46). ASIC3 expression has been previously reported in normal NG, as well as PG (13).…”
Section: L988 Asic Expression In Chemoafferent Neuronssupporting
confidence: 57%
“…It was also reported that "intercluster spaces" were devoid of staining, suggesting that ASIC are not present in nerve fibers and terminals (46). However, these latter results cannot be considered conclusive because the exquisitely slender nerve fibers and terminals that form synapses are not distinct from type I cells in immunofluorescence preparations.…”
Section: L988 Asic Expression In Chemoafferent Neuronsmentioning
confidence: 95%
“…[1][2][3][4] But, work soon progressed to the molecular and genetic level, with Abboud's particular focus being the form and function of baroreceptor neurons. [5][6][7][8][9] As Abboud explained in a recent interview, however, research is just one third of his professional passion. He is also, in equal parts, a dedicated physician and mentor..…”
Section: Profiles In Cardiovascular Sciencementioning
confidence: 99%
“…First, carotid body glomus cells express ASIC1 and ASIC3 and, to a lesser extent, ASIC2. 42 Second, carotid body glomus cells have pH-gated currents that resemble ASIC channels and are partially amiloride sensitive. 42 Third, cardiovascular responses to chemoreceptor stimulation with carotid artery occlusion are attenuated in ASIC3 and ASIC1/ASIC3 double-null mice.…”
Section: Role In Cardiovascular Chemosensationmentioning
confidence: 99%
“…42 Second, carotid body glomus cells have pH-gated currents that resemble ASIC channels and are partially amiloride sensitive. 42 Third, cardiovascular responses to chemoreceptor stimulation with carotid artery occlusion are attenuated in ASIC3 and ASIC1/ASIC3 double-null mice. 43 Together these findings suggest that ASIC proteins may participate in pH sensing in arterial chemoreceptors.…”
Section: Role In Cardiovascular Chemosensationmentioning
confidence: 99%